Issues in implementing electronic tendering in Indonesian’s construction industry - Ratih Kusumawati, Ratih Kusumawati (2012)
Electronic tendering is actually the advent of Information Communication Technology (ICT) in construction industry, whereby it has brought a broad exploration to the use of web-based technology in tendering process. Electronic tendering, in its simplest form, is described as the electronic publishing, communicating, accessing, receiving and submitting of all tender-related information and documentation via the internet, thereby replacing the traditional paper-based tender processes, and achieving a more efficient and effective business process for all parties involved. Currently, Indonesian’s government is increasing efforts to bring all government procurement processes through electronic tendering. Electronic tendering is relatively new approach brought a new perspective in construction industry in Indonesia. Based on Presidential Regulation (Perpres) No.54/2010, by 2012, all government institutions (central and local) must implement e-procurement for partly or whole packages. Undoubtedly, there will be many barriers challenging the successful implementation of electronic tendering system. Therefore, the objective of the study is to determine the possible issues of electronic tendering implementation in Indonesian’s government project. To meet that objective, the analysis was done mainly through an extensive literature review of various national and international publications, legislation and court decisions that are relevant with electronic tendering. By analyzing the relevant case law, the issues in implementing electronic tendering are identified. The issues arise in electronic tendering system are not significantly different from paper based tendering system. The issues are relate to whether the tender is considered as conforming or non-conforming in electronic environment.